2021
DOI: 10.1108/ijlss-03-2021-0057
|View full text |Cite
|
Sign up to set email alerts
|

A foundational framework for agile enterprise architecture

Abstract: Purpose The application of agility principles and methodologies on Enterprise Architecture (EA) is a promising field. This paper aims to provide an in-depth study of the Agile Enterprise Architecture (AEA) by studying EA practitioners’ perspectives to propose a foundational framework for AEA. Design/methodology/approach The authors formulate a foundational framework that defines the AEA motivators, enablers and blockers using the agile manifesto as one of the AEA enablers where a total of 156 EA stakeholders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The organization's size, its reliance on its enterprise architecture, and its awareness of agile practices significantly influence this favorable perception. 58 The outcomes also highlight that the willingness of both the business and IT sectors to embrace change stands out as the principal driving force behind the adoption of agile approaches in enterprise design. 58,59 In a study by Van Wessel et al, 60 The authors demonstrated the synergy between enterprise design and agile development through an examination of five case studies encompassing IT-based projects within both corporate and governmental contexts.…”
Section: 21mentioning
confidence: 99%
See 3 more Smart Citations
“…The organization's size, its reliance on its enterprise architecture, and its awareness of agile practices significantly influence this favorable perception. 58 The outcomes also highlight that the willingness of both the business and IT sectors to embrace change stands out as the principal driving force behind the adoption of agile approaches in enterprise design. 58,59 In a study by Van Wessel et al, 60 The authors demonstrated the synergy between enterprise design and agile development through an examination of five case studies encompassing IT-based projects within both corporate and governmental contexts.…”
Section: 21mentioning
confidence: 99%
“…58 The outcomes also highlight that the willingness of both the business and IT sectors to embrace change stands out as the principal driving force behind the adoption of agile approaches in enterprise design. 58,59 In a study by Van Wessel et al, 60 The authors demonstrated the synergy between enterprise design and agile development through an examination of five case studies encompassing IT-based projects within both corporate and governmental contexts. Their recommendation to organizations was to integrate specific elements from both approaches.…”
Section: 21mentioning
confidence: 99%
See 2 more Smart Citations
“…And considering lines of events since 2020, the timeframe for many companies is in the area of 7 -30 days from early indications to stable solutions. Using agile principles and methods in enterprise architecture has attracted some interest (Rouhani et al, 2008;Buckl et al, 2011;Alzoubi et al, 2015;Kaddoumi and Watfa, 2016;Kaddoumi and Watfa, 2021). Defining enterprise architecture has been the subject of multi-faceted publications and research initiatives.…”
Section: Theoretical Backgroundmentioning
confidence: 99%